Dwarfism and Altered Craniofacial Development in Rabbits Is Caused by a 12.1 kb Deletion at the HMGA2 Locus. Issue 2 (1st February 2017) - Carneiro, Miguel; Hu, Dou; Archer, John; Feng, Chungang; Afonso, Sandra; Chen, Congying; Blanco-Aguiar, José A; Garreau, Hervé; Boucher, Samuel; Ferreira, Paula G; Ferrand, Nuno; Rubin, Carl-Johan; et al.
Abstract: The dwarf phenotype characterizes the smallest of rabbit breeds and is governed largely by the effects of a single dwarfing allele with an incompletely dominant effect on growth. Dwarf rabbits typically weigh under 1 kg and have altered craniofacial morphology. The dwarf allele is recessive lethal and dwarf homozygotes die within a few days of birth. The dwarf phenotype is expressed in heterozygous individuals and rabbits from dwarf breeds homozygous for the wild-type allele are normal, although smaller when compared to other breeds. Here, we show that the dwarf allele constitutes a ∼12.1 kb deletion overlapping the promoter region and first three exons of the HMGA2 gene leading to inactivation of this gene. HMGA2 has been frequently associated with variation in body size across species. Homozygotes for null alleles are viable in mice but not in rabbits and probably not in humans. RNA-sequencing analysis of rabbit embryos showed that very few genes (4–29 genes) were differentially expressed among the three HMGA2/dwarf genotypes, suggesting that dwarfism and inviability in rabbits are caused by modest changes in gene expression. Our results show that HMGA2 is critical for normal expression of IGF2BP2, which encodes an RNA-binding protein. Finally, we report a catalog of regions of elevated genetic differentiation between dwarf and normal-size rabbits, including LCORL-NCAPG, STC2, HOXD cluster, and IGF2BP2 . Levels and patterns of genetic diversity at the LCORL-NCAPG locus further suggest that small size in dwarf breeds was enhanced by crosses with wild rabbits. Overall, our results imply that small size in dwarf rabbits results from a large effect, loss-of-function (LOF) mutation in HMGA2 combined with polygenic selection.